2016
DOI: 10.18632/oncotarget.9222
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation proteasome inhibitor oprozomib synergizes with modulators of the unfolded protein response to suppress hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) responds poorly to conventional systemic therapies. The first-in-class proteasome inhibitor bortezomib has been approved in clinical use for hematologic malignancies and has shown modest activity in solid tumors, including HCC. However, a considerable proportion of patients fail to respond and experience important adverse events. Recently, the next-generation orally bioavailable irreversible proteasome inhibitor oprozomib was developed. Here, we assessed the efficacy of oprozomib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition to the canonical Atf6α downstream response leading to expanded ER proteosynthetic capacity, and the extensive evidence that Atf6α modulates cell survival, some studies have found that Atf6α action also influences the decision to enter the cell cycle. Some of the work implicating Atf6α in proliferation has been performed in cancer or cancer cell lines [117], [118], [119], [120], [121], [122]; other observations are in primary tissues such as pancreatic beta cells, ovarian cells, chondrocytes and cardiomyocytes [46], [92], [123], [124], [125]. In most cases, Atf6α activation increased cell cycle entry, whether as part of healthy tissue growth and adaptation or as a maladaptive response to disease.…”
Section: Atf6α Also Modulates Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the canonical Atf6α downstream response leading to expanded ER proteosynthetic capacity, and the extensive evidence that Atf6α modulates cell survival, some studies have found that Atf6α action also influences the decision to enter the cell cycle. Some of the work implicating Atf6α in proliferation has been performed in cancer or cancer cell lines [117], [118], [119], [120], [121], [122]; other observations are in primary tissues such as pancreatic beta cells, ovarian cells, chondrocytes and cardiomyocytes [46], [92], [123], [124], [125]. In most cases, Atf6α activation increased cell cycle entry, whether as part of healthy tissue growth and adaptation or as a maladaptive response to disease.…”
Section: Atf6α Also Modulates Cell Proliferationmentioning
confidence: 99%
“…Although the majority of studies investigating ATF6α in cancer cells have focused on oncogenic cell survival in the face of ER stress, there is evidence that ATF6α promotes proliferation as well. ATF6α, known to be a tumorigenic factor in hepatocellular carcinoma [130], drives proliferation and BrdU incorporation in hepatoma cells in a proteostasis-stress dependent manner [118]. Treating cells with a proteasome inhibitor oprozomib decreased proliferation by inhibiting regulated intramembrane proteolysis, thus reducing ATF6α cleavage and decreasing ATF6α target gene activation [118].…”
Section: Atf6α Also Modulates Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Small chemical chaperones reducing ER stress are capable of ameliorating methionine and choline deficient diet-induced steatohepatitis [7], acetaminophen-induced hepatotoxicity [8], CCl 4 -induced liver fibrosis [9], ischemia-reperfusion-induced liver injury [10], and diethylnitrosamine-induced hepatic carcinogenesis [11]. Thus, it has been proposed the amelioration of ER stress is essential for maintaining liver homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that NFV acts as an inhibitor of HSP90 and causes unfolded protein response and ER stress [137]. Moreover, it synergizes with proteosome inhibitors to suppress cancer cells [138][139][140]. Interestingly, a recent study demonstrated that as NFV inhibits thyroid cancer cell proliferation and migration, it also induces DNA damage and sensitizes cells to anoikis, suggesting that it could be a new promising therapeutic agent for TC [26,141].…”
Section: Other Putative Noasmentioning
confidence: 99%